2015
DOI: 10.5430/ijhe.v4n1p217
|View full text |Cite
|
Sign up to set email alerts
|

Are Teacher Course Evaluations Biased Against Faculty That Teach Quantitative Methods Courses?

Abstract: The present study investigated graduate students' responses to teacher/course evaluations (TCE) to determine if students' responses were inherently biased against faculty who teach quantitative methods courses. Item response theory (IRT) and Differential Item Functioning (DIF) techniques were utilized for data analysis. Results indicate students in non-methods courses preferred the structure of quantitative courses, but tend to be more critical of quantitative instructors. Authors encourage consumers of TCE re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…8 Age, [11], charisma [13], and physical attractiveness [14,15] are also associated with SET. Other factors generally not in the instructor's control that may affect SET scores include class time, class size, mathematical or technical content [16], and the physical classroom environment [17]. Many studies cast doubt on the validity of SET as a measure of teaching effectiveness (see Johnson [4, for a review and analysis, Pounder [18] for a review, and Galbraith et al [19], Carrell and West [2] for exemplars).…”
Section: Discussion Other Studiesmentioning
confidence: 99%
“…8 Age, [11], charisma [13], and physical attractiveness [14,15] are also associated with SET. Other factors generally not in the instructor's control that may affect SET scores include class time, class size, mathematical or technical content [16], and the physical classroom environment [17]. Many studies cast doubt on the validity of SET as a measure of teaching effectiveness (see Johnson [4, for a review and analysis, Pounder [18] for a review, and Galbraith et al [19], Carrell and West [2] for exemplars).…”
Section: Discussion Other Studiesmentioning
confidence: 99%
“…Other researchers used Rasch models to identify biases that may threaten the interpretation of SET results. Royal and Stockdale (2015) investigated SET ratings to determine if response biases were detected in courses relating to quantitative methods and approaches. Similarly, Haladyna and Hess (1994) applied a Rasch model to identify and correct biases in data that included faculty member, item rater, gender of rater, rater perception of course type, and whether course was required or elective.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this sense, it has been confirmed that in undergraduate courses, the area of knowledge induces a considerable bias in SETs ( Cashin, 1990 ; Beran & Violato, 2005 ; Centra, 2009 ; Uttl, White & Morin, 2013 ; Royal & Stockdale, 2015 ; Uttl & Smibert, 2017 ; Arroyo-Barrigüete et al, 2021 ). Furthermore, it is also clear that this bias has relevance, regardless of the percentage of the variance explained by that factor.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, the recent work by Uttl & Smibert (2017) highlights that a particularly relevant noninstructional bias, the subject area to which the course belongs, has likely been undervalued in many previous studies. Numerous articles have found a negative bias toward teachers who teach quantitative and/or STEM courses ( Cashin, 1990 ; Beran & Violato, 2005 ; Centra, 2009 ; Uttl, White & Morin, 2013 ; Royal & Stockdale, 2015 ; DeFrain, 2016 ; Rosen, 2018 ; Arroyo-Barrigüete et al, 2021 ), but Uttl and Smibert claim that in several of these articles, the relevance of this bias is underestimated. They stated that parametric statistics are not appropriate due to several factors.…”
Section: Introductionmentioning
confidence: 99%